Causes of death in children younger than five years in China in 2015: an updated analysis - Song, Peige (The University of Edinburgh, 2016)
Introduction Since the adoption of the Millennium Development Goals (MDGs) in 2000, substantial progress in improving child health and reducing child mortality rate has been made in the last one and half decades. Despite the achievements, for a populous county like China, there are still 181,574 children under five years old who died in 2015, most of them were preventable. Under the new Sustainable Development Goals (SDGs), information about the distribution of causes of death and time trend for child mortality should be updated to inform policy and research. In this study, I aim to estimate the causes of death in children younger than five years old in recent seven years from 2009 to 2015 with a focus on the year of 2015 and provide an update causes of death predicting model for China. Methods Updated data of under-five mortality rates and number of live births at national and provincial levels were obtained from the National Maternal and Child Mortality Surveillance System, the National Maternal and Child Health Annual Reporting System and the Chinese Bureau of Statistics by systematically searching, and then adjusted by United Nation's Inter-agency Group for Child Mortality Estimation. A systematic review was also conducted from high-quality community based longitudinal studies of different causes of death in three Chinese and one English bibliographic databases, a single proportionate cause-of-death modelling based on the Child Health Epidemiology Reference Group method was developed to estimate the number of child death according to proportional causes in different age group at both national and provincial levels. Results Of all children died before five years old in 2015 in China, 51.5% occurred during the first month, 21.6% occurred during 1-12months, and 27.6% were from 1-4 years old. The leading causes of death in 2015 were preterm birth complications, birth asphyxia, congenital abnormalities and pneumonia for children under five years old. Different models were constructed for different age group which can be applied to predict the proportional distribution of causes of death for the following years. The causes of death spectrum changed dramatically among different provinces with different development levels, especially for the proportions of infectious diseases and congenital abnormalities. Conclusions As an update analysis, this study validates the accuracy of the previous study and proposes a new statistical modelling method to predict the proportions of most common causes of child death in China which can be adopted in further related studies. Furthermore, this study offers the most up-to-date estimates of causes of child death in China from 2009 to 2015, with these estimates, targeting strategies on reducing child mortality, especially for neonates, should be made toward the top causes of neonatal diseases, congenital abnormalities, and infectious diseases, with special attentions on the difference between different regions with uneven development levels.
Keywords: cause of death; childhood mortality; child health; infant health; China; infant mortality